Corporate Events, Trading Activity, and the Estimation of Systematic Risk: Evidence From Equity Offerings and Share Repurchases. - Denis, David J; Kadlec, Gregory B (Journal of Finance, 1994)
The authors investigate the relation between trading activity, the measurement of security returns, and the evolution of security prices by examining estimates of systematic risk surrounding equity offerings and share repurchases. In contrast to prior studies, they find no evidence of changes in systematic risk following either equity offerings or share repurchases after correcting for biases caused by infrequent trading and price adjustment delays. Moreover, changes in ordinary least squares beta estimates are significantly related to contemporaneous changes in trading activity. The authors' results have implications for studies interested in the properties of security returns, particularly those examining periods in which trading activity changes.